Antiviral Effects of Garlic (Allium sativum) and Nilavembu (Andrographis paniculata) against Velogenic Strain of Newcastle Disease Virus: An In ovo Study** - Toryali Arify; Jaisree, S.; Manimaran, K.; Ezhil Valavan, S.; A. Sundaresan (International Journal of Livestock Research, 2018)
The research work was conducted to evaluate antiviral effects of garlic (Allium sativum) and nilavembu (Andrographis paniculata) against Newcastle disease virus. Different concentrations (10 mg / ml, 50 mg / ml, 100 mg / ml and 200 mg / ml) of aqueous garlic extract, aqueous nilavembu extract, 50 % ethanol extract of nilavembu and 100 % ethanol extract of nilavembu were prepared. Lethality study of these extracts was carried out in embryonated chicken eggs (ECE). No lethality was observed up to 200 mg/ml and 100 mg / ml concentration of nilavembu and garlic extracts, respectively. Antiviral activity of different concentration of garlic and nilavembu extracts were added by virus neutralization test in ECE with velogenic strain of Newcastle disease virus (VNDV) in 8 group of birds. The group IX was kept as positive control by inoculating 0.2ml of VNDV and group X was kept as negative control by adding 0.2ml PBS. This study revealed that aqueous extract of nilavembu at higher concentration (100 mg / ml) and ethanol extract of nilavembu (10 mg / ml and 100 mg / ml) were found to have good antiviral property against Velogenic strain of Newcastle disease.